Emergence of IT sector in India and Gujarat - Rucha Naldurgakar; Sonal Umesh Patil; Jahanvi Sharma (MultiTech Publisher, 2023)
After independence a new sector was born in India, The IT-ITeS industry, which stands for information technology and information services, has emerged as the cornerstone of contemporary India. Including hardware, software, and telecommunications, IT is a commercial area that deals with computing. India is regarded as the information hub and is the driving force behind the spread of information technology around the world. The Indian economy is dependent on IT sector, which contributes completely on the GDP (7.4%in financial year 2022, according to statista) and wellness of the country. As Gujarat is the major industrial state in India and also providing favorable business environment backed by several key principles of business copy (EODB) and business processes. In the global IT sector, the India has comparative advantage in term of cost. It can improve the productivity and efficiency in other industry.